Interaction Second Virial Coefficients of Non-spherical Molecules - Haghighi, Behzad; Farhami, Nabieh (Asian Journal of Chemistry, 2016)
A revised analysis of the effect of long-range non-spherical terms in the intermolecular potential on the interaction second virial coefficient is presented with a preferred realistic potential functions-proposed for the molecular gases and their mixtures of noble gases-for spherical core treatment of integration in the small regions of intermolecular distances. The paper presents a contribution to the interaction second virial coefficient due to the asphericity of the molecular charge distribution. Results from calculating the non-spherical contribution to the interaction second virial coefficient with a realistic spherical core are obtained from statistical mechanics and applied to the pure system such as O2-O2 and H2-H2 and mixtures such as N2 + He, N2 + Ar, O2 + He, O2 + He, O2 + Ar, H2 + He, H2 + Ne, H2 + Ar and H2 + Kr.